Infections, infertility, and assisted reproduction - Elder, Kay 1946- (Cambridge University Press, 2004)
ART treatment is vulnerable to the hazard of potential infection from many different sources: patients, samples, staff and the environment. Culture of gametes and embryos in vitro provides multiple targets for transmission of potential infection, including the developing embryo, neighbouring gametes and embryos, the couple undergoing treatment and other couples being treated during the same period. This unique situation, with multifaceted opportunities for microbial growth and transmission, makes infection and contamination control absolutely crucial in the practice of assisted reproduction, and in the laboratory in particular. Originally published in 2004, this practical book provides a basic overview of microbiology in the context of ART, providing a guide to infections in reproductive medicine. The relevant facets of the complex and vast field of microbiology are condensed and focused, highlighting information that is crucial for safe practice in both clinical and laboratory aspects of ART.